Theory and Application of an Optimizing Procedure for Lock Box Location Analysis - Nauss, Robert M.; Markland, Robert E. (Management Science, 1981)
This paper describes the theory, development, and application of an optimizing procedure for solving lock box location problems. Such problems have become increasingly important to banks, corporations, and governmental agencies in their quest for more efficient cash management. Extensive discussion of practical data collection and modeling aspects is provided. An optimizing procedure for solving the problem is discussed, and computational results are reported.